2012
DOI: 10.1071/mf12016
|View full text |Cite
|
Sign up to set email alerts
|

Small home range in southern Australia's largest resident reef fish, the western blue groper (Achoerodus gouldii): implications for adequacy of no-take marine protected areas

Abstract: No-take marine protected areas (MPAs) represent an effective biodiversity conservation tool for a range of species including resident reef fishes that are intrinsically vulnerable to overfishing and other localised impacts. The western blue groper (Achoerodus gouldii) is the largest permanent-resident reef teleost in southern Australian waters and has the second-oldest recorded age of any labrid at 70 years. Acoustic telemetry was used to investigate whether adult A. gouldii can be effectively protected within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Some fish species show clear resident movement patterns [64], [76], [77] while others have different individual movement dynamics [28], [78], [79]. In our study, we observed that the behavioral patterns of white seabream differed not only between resident and transient fish, but also in the diel habitat use of resident individuals.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Some fish species show clear resident movement patterns [64], [76], [77] while others have different individual movement dynamics [28], [78], [79]. In our study, we observed that the behavioral patterns of white seabream differed not only between resident and transient fish, but also in the diel habitat use of resident individuals.…”
Section: Discussionmentioning
confidence: 49%
“…Payne et al [54] showed that the observed diel detection pattern of cuttlefish ( Sepia apama ) was solely due to fluctuating diel detection probabilities, which decreased at night due to environmental noises. Since that work, some studies have integrated control tags into their study design to validate their detection patterns [27], [64]. Diel variations of detection probabilities were notably noticed in the study of Bryars et al [64], carried out on a heterogeneous coastal reef with sandy bottoms and seaweed along Kangaroo Island in South Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we calculated a Residency Index (RI) [9], [37] to give an estimate of site fidelity. This was calculated as the number of detection days for each fish on any given receiver divided by the total number of possible detection days, multiplied by one hundred to express as a percentage.…”
Section: Methodsmentioning
confidence: 99%
“…This is the case for many species belonging to the families Cheilodactylidae (Lowry and Suthers 1998), Cottidae (Mireles et al 2012), Labridae (Barrett 1995;Arendt et al 2001;Edgar et al 2004;Topping et al 2005;Bryars et al 2012), Monacanthidae (Barrett 1995;Edgar et al 2004), Pempheridae (Annese and Kingsford 2005), Pinguipedidae (Mace and Johnston 1983;Cole et al 2000;Carbines and McKenzie 2004), Scorpaenidae (Matthews et al 1987), Sebastidae (Jorgensen et al 2006;Green and Starr 2011), Serranidae (Lembo et al 1999;Lowe et al 2003;Irigoyen 2010), Sparidae (Willis et al 2001;Griffiths and Wilke 2002;Parsons et al 2003;Kerwath et al 2007), and Syngnathidae (Connolly et al 2002;Moreau and Vincent 2004). The ubiquitousness of reduced mobility in temperate reef species suggests that MPAs, as well as other spatial management strategies, may be adequate tools for protecting these species (Gunderson et al 2008).…”
Section: Introductionmentioning
confidence: 99%